Stock Price Prediction in Bursa Malaysia - Nurfadhlina Binti Abdul Halim; Goh Khang Wen (Program Studi Statistika Unisba, 2007)
Investment in stock is a highly risky investment, it is because the existence of randomness in thestock price. In lecture, usually we used Binomial model to price the stock. But, in real world, how dowe price the stock? Because the stock price is random, the volatility and drift is a crucial items tobehold. The main questions is how to calculate this volatility and drift, and the answer to thequestion is the sample variance and the sample mean. At any time, the stock price will be either up ordown from the previous price. This is where we need a method or model to calculate parameters forup-state and down-state for the stock price. And it will cover the volatility and the drift in anembrace. The method we used in this paper is the Hull-White algorithm. Hull-White algorithm is tofind the parameters value of u and d for prediction to stock price. Using SPSS, we will run the data toget the sample variance and sample mean. Then, using Maple 10, we calculate the u and d beforeenter the value of u and d into programming C++.